INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE: A CASE OF UNIVERSITIES IN MACHAKOS AND KITUI COUNTIES, KENYA - MBITI, ANNAH M. (My University, 2019)
The purpose of this study was to examine the influence of human resource management practices on organizational performance: A case of Universities in Machakos and Kitui Counties in Kenya. The specific objectives were to examine; the influence of staffing on performance of universities, the influence of training programs on performance of universities, the influence of performance appraisal on performance of universities and the influence of succession planning on performance of universities. A descriptive research design was adopted targeting staff working in the Universities located in Machakos and Kitui Counties. Descriptive design was suitable because it is used to describe some aspects or characteristics of human population such as opinions, attitudes, beliefs or even knowledge of certain phenomenon without influencing their behavior. There are four fully fledged Universities operating in Machakos and Kitui Counties. The target population comprised of staff in the administration, human resource, finance and audit, procurement, deans of schools and directorate of quality assurance totaling to 263. The selected departments play important roles in ensuring high academic standards, sound financial position and effective implementation of organizational policies and their competencies are required in shaping the performance of the universities. Since the study population was heterogeneous the study used stratified sampling, using departments as the strata basis. Stratified sampling helped in obtaining several mutually exclusive strata which assisted in providing adequate data for analyzing the various sub population. Stratified random sampling was used in each stratum, 10 – 30% of the population was used to get sample size and the study used 17% which was 45. Questionnaire with both open and closed ended questions was used to collect data. The data was analyzed using descriptive statistics that is frequencies, percentages and means. Inferential statistics involving correlation analysis, multiple linear regression analysis and Analysis of Variance (ANOVA) were used to address the objectives of the study. The study found out that when the right blend of employees is brought on board from the beginning, the universities stood a better chance of recording high performance compared to their competitors. The study also revealed that when you train university employees on all aspects of their job and give them insight into other positions in the university, develop well-rounded individuals who have a working knowledge of their positions and those of their colleagues. Knowledgeable employees are better able to answer customer questions, handle problems and deliver better quality services. From the study findings, it was noted that monitoring and evaluating staff at regular intervals helped them to establish their weaknesses or strengths and work on them accordingly towards achieving the organizational performance. Lastly, the study found out that when the talents of the internal staff are nurtured and developed, it helped the universities in experiencing a smooth transition of staff. The study recommends that staffing that includes recruitment and selection should be done in a systematic, transparent and strategic way that should help the universities management in Machakos and Kitui Counties to acquire the right candidates with the required competence and abilities to assist in achieving the organizational objectives. Relevant training programs should cut across all employees to encourage their participation and reduce their demotivation which can result in high staff turnover. Clear job descriptions for each staff should be well spelt out which will guide in appraising the employees. This will avoid confusion and dissatisfaction of employees because they do not understand what is expected of them which may result in failure in meeting their set targets. Lastly, the university management should incorporate succession planning in their strategic plan to focus on the term of employee transitions.
Keywords: Human resource management